2013
DOI: 10.1097/qad.0b013e32835f2b7a
|View full text |Cite
|
Sign up to set email alerts
|

Development of sulphated and naphthylsulphonated carbosilane dendrimers as topical microbicides to prevent HIV-1 sexual transmission

Abstract: These interesting results suggest that G3-S16 or G2-NF16 could be effective to inhibit HIV infection and transmission within genital mucosa as well as the spread of HIV transmission to human PBMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…17 Briefly, prechilled Vero cell monolayers in 24-well plates (175×10 3 cells/well) were treated with dendrimers for 1 hour at 4°C and infected with 150 PFU/well HSV-2 for 2 hours at 4°C. Cells were washed with cold 2% FBS/DMEM to remove unattached dendrimers and unabsorbed HSV-2 and overlaid with medium containing human Ig.…”
Section: Attachment Assaymentioning
confidence: 99%
See 4 more Smart Citations
“…17 Briefly, prechilled Vero cell monolayers in 24-well plates (175×10 3 cells/well) were treated with dendrimers for 1 hour at 4°C and infected with 150 PFU/well HSV-2 for 2 hours at 4°C. Cells were washed with cold 2% FBS/DMEM to remove unattached dendrimers and unabsorbed HSV-2 and overlaid with medium containing human Ig.…”
Section: Attachment Assaymentioning
confidence: 99%
“…Previously, we showed that both dendrimers did not induce vaginal irritation or inflammation in BALB/c mice and they were well tolerated for topical application. 8,17,31 Female BALB/c mice (20±2 g) that were 6-8 weeks old were housed at the CBMSO. Animal studies were conducted and approved by the CBMSO Institutional Animal Care and Use Committee (CEEA-CBMSO, Madrid, Spain).…”
Section: In Vivo Vaginal Challenge Assaymentioning
confidence: 99%
See 3 more Smart Citations